THE PALAEOENVIRONMENTS AND DEPOSITIONAL MODEL FOR THE NGRAYONG SANDSTONES AN OUTCROP STUDY IN EASTERN PART OF THE MADURA ISLAND AS A REFERENCE - MAC. Endharto (Testing Center for Oil and Gas LEMIGAS, 2006)
This topic is the most eastern portion of the se- ries depositional model of the Ngrayong Sandstone, which well develops particularly in Madura Island. This study is also observing both vertical and horizontal sequences of the sedintentological aspects and its geological associations of the Ngrayong Sandstone outcrops. The eastern part is situated between 06° 58' 10